Study of silty sand slope protection from seepage flows using short fiber-sand mixtures. Issue 5 (18th October 2021) - Bao, X.; Li, L.; Liao, Z.; Cui, H.; Tang, W.; Chen, X.
Abstract : Silty sand slopes are prone to damage due to seepage or rainfall. A partial reinforcement method using short polypropylene fiber and sand mixtures was proposed to protect silty sand slopes from seepage flow failure. The effects and the reinforcement mechanism were explored. First, triaxial tests were performed on sand samples reinforced with fiber lengths (6 and 12 mm) and contents (0.25 and 0.50%) to verify the reinforcement effect. Then, model tests were conducted on sand slopes under lateral seepage flow and the failure mode with different fiber contents and reinforcement method were examined. The results showed that the cohesion and shear strength of sand were significantly improved with the increase of fiber content and length. The suction of unsaturated sand was also enhanced by the fibers. The change in stress-strain behavior from strain softening to strain hardening indicated that static liquefaction could be effectively prevented. The failure mode and extent of slope damage depended on the fiber content. However, it was noted that the slope surface with small reinforcement range performed similarly to that with large reinforcement range. In conclusion, the partial reinforcement method with short discrete synthetic fibers can be used as an effective alternative for slope reinforcement.